Accounting Ethics And Corporate Accountability In The Extractive Industry Evidence From PT Freeport Indonesia - Masnawaty Sangkala (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study examines ethical accountability and professional accounting ethics within the context of PT Freeport Indonesia, one of the largest mining companies operating in Indonesia. The research investigates three key issues: the forms of ethical misconduct associated with the company, the accounting ethics principles affected by these practices, and their implications for corporate accountability and stakeholder trust. Drawing upon Stakeholder Theory and Legitimacy Theory, the study adopts a qualitative case study approach and utilizes secondary data collected from corporate reports, government publications, academic literature, media reports, and non-governmental organization documents. The data were analyzed using thematic analysis to identify recurring patterns related to environmental responsibility, transparency, governance practices, and stakeholder welfare. The findings reveal four major categories of ethical concerns, namely environmental accountability issues, transparency and disclosure concerns, governance-related controversies, and stakeholder welfare issues. The analysis indicates that these concerns are associated with violations of professional responsibility, integrity, objectivity, and public interest principles within the accounting ethics framework. The study also demonstrates that ethical controversies may generate regulatory consequences, reputational risks, and challenges to organizational legitimacy, ultimately affecting stakeholder trust and long-term sustainability. The findings contribute to the accounting ethics and corporate accountability literature by highlighting the interconnected nature of environmental, social, and governance responsibilities in the extractive industry. The study emphasizes the importance of transparency, ethical governance, stakeholder engagement, and sustainable business practices in strengthening organizational accountability and maintaining public legitimacy.